Towards a psychoanalytic migration studies: A son, a brother, a father, an American, and his house in a Cameroonian village - Page, Ben (Migration studies, 2021)
Abstract Around the world, migrants are building houses in their countries-of-origin. For the women and men who create them, these houses are unambiguously significant. Yet, in academic migration studies, they are often seen as peripheral—interesting rather than important. This article follows recent work that aims to show why these houses really do matter. These houses are where migrants can seek to process the trauma of the disconnection that is inherent in migration and are how they repress the anxieties that arise from transnationalism. Migrants’ emotions are externalised onto the house. Based on ethnographic fieldwork in Cameroon between 2013 and 2018, this article develops a case study about one transnational migrant, his family, and his house. It uses the example to develop two arguments: first that these houses sit within transnational networks, but the networks are subject-centred so a theory of the subject is needed to analyse them. Secondly, that human subjects make a deal when they exchange infantile egocentrism for collective inter-subjectivity, which is similar to the deal made between transnational migrants and their ancestral home when they receive permission to leave in exchange for continuing to connect—a link that is materialised in the house. Both these arguments combine to support an underlying claim that migration studies in general, and studies of migrant housing in particular would benefit from building further on existing work that draws on psychoanalytical approaches.